Hematopoietic-Specific Deletion of Foxo1 Promotes NK Cell Specification and Proliferation - Huang, Pei; Wang, Fangjie; Yang, Yao; Lai, Wenjing; Meng, Meng; Wu, Shuting; Peng, Hongyan; Wang, Lili; Zhan, Rixing; Imani, Saber; Yu, Jianhua; Chen, Bingbo; et al. (Frontiers in Immunology, 2019)
We previously reported that deletion of Foxo1, via Ncr1-iCre mice from the expression of NKp46 onward, led to enhanced natural killer (NK) cell maturation and effector function. In this model, however, the role of Foxo1 in regulating NK cell specification and early development remains exclusive. Herein, we utilized a murine model of hematopoietic-specific deletion of Foxo1 before lymphoid specification, by crossing mice carrying floxed Foxo1 alleles (Foxo1fl/fl) with Vav1-iCre mice, to revisit the role of Foxo1 on NK cell specification and early development. The data showed that hematopoietic-specific deletion of Foxo1 resulted in increased proportion and numbers of common lymphoid progenitors (CLP) (Lin−CD127+Ckit+Sca-1+), re-pro NK b cells (Lin−Sca-1+c-kit−CD135−CD127+), as well as committed Lin−CD122+ cells and CD3−CD19−NKp46+ NK cells in bone marrow. Hematopoietic-specific deletion of Foxo1 also promoted NK cells proliferation in a cell-intrinsic manner, indicated by increased Ki-67 expression and more expansion of NK cell after ex vivo stimulation with IL-15. The reason for Foxo1 suppressing NK cell proliferation might be its direct transcription of the cell-cycle inhibitory genes, such as p21cip1, p27kip1, p130, Gadd45a and Ccng2 (cyclin G2) in NK cells, supported by the evidence of decreased mRNA expression of p21cip1, p27kip1, p130, Gadd45a and Ccng2 in Foxo1-deficient NK cells and direct binding of Foxo1 on their promoter region. Furthermore, hematopoietic-specific deletion of Foxo1 resulted in increased ratio of mature NK subsets, such as CD11b+CD27− and CD43+KLRG1+ NK cells, but decreased ratio of immature NK subsets, such as CD27+CD11b− and CD27+CD11b+ NK cells, consistent with the findings in the murine model of Ncr1-iCre mediated Foxo1 deletion. Conclusively, Foxo1 not only acts as a negative checkpoint on NK cell maturation, but also represses NK cell specification and proliferation. The relative higher expression of Foxo1 in CLP and early NK precursors may also contribute to the later NK cell proliferation and responsiveness, which warranties another separate study in the future.